Stress and coping strategies among police personnel at selected police stations in Kathmandu Valley. - Lohala, Sagun (2020)
ABSTRACT : Police personnel are those who are on continuous contact to stressful situation ranging from social issues, road traffic accidents to natural calamities. The objective of this study was to assess stress and coping strategies among police personnel in the selected police stations of Kathmandu Valley. A descriptive cross-sectional study design was used. Non-probability consecutive sampling technique was adopted for selection 198 police personnel from selected police stations. A structured self-administered questionnaire containing questions related to socio-demographic characteristics and Police Stress Questionnaire and Brief COPE (Coping Orientation to Problems Experienced) scale was used as to measure stress and coping strategies. Descriptive statistics was used to describe socio-demographic characteristics, level of stress and coping strategies whereas chi- square test was used to determine the association between variables. The findings indicated that more than half (56.1%) of the police personnel had high level of operational stress and nearly half (45.0%) had high level of organizational stress. There was significant association found between age and organizational stress with (p=.003). Similarly, duration of work was significantly associated with levels of operational and organizational stress with p-value .002 and < .001 respectively. Problem focused coping were being used by more than two third (69.125%) of respondents. Positive reframing coping strategies are the most rated coping strategy (72.66%). There is significant relationship between operational and organizational stress. All types of coping strategies are significantly correlated with each other. It is concluded that more than half of the police personnel involved in the study tends to have operational and organizational stress respectively. Those police personnel tend to use problem focused coping strategies more than emotion focused and dysfunctional coping strategies. Hence, there is need for programs to decrease job stress among police personnel in order to prevent physical and mental consequences. Key words: Stress, Coping Strategies, Police personnel